Review in deep processing of whey - Zhansaya A. Abish; Ravshanbek S. Alibekov; Maria Tarapoulouzi; Asem R. Bakhtybekova; Ziba I. Kobzhasarova (Cogent Food & Agriculture)
Whey is a natural by-product of the production of cheese, cottage cheese and milk protein concentrate. The draining of whey remains a significant environmental pollutant. Review of some recent studies on the production of innovative new products are presented, as they favorably affect the human body, animals, and the environment. Specifically, three types of whey proteins productions are available: whey protein concentrate (WPC), whey protein isolate (WPI) and whey protein hydrolysate (WPH) consist in essential amino acids and bioactive peptides. Lactic, nucleic, hyaluronic and volatile fatty acids such as acetic, formic, propionic and butyric acids are in the whey. High solubility, water adsorption, gelation and emulsifying properties are important factors that make whey protein functional food additives. Bioactive peptides have antioxidant, antidiabetic and anti-cancer properties as well and can prevent obesity and reduce blood pressure. Composition and properties of whey are considered, including: protein content, obtaining peptides, various acids, functional beverages, animal feed and biodegradable polymers from whey. Modern technologies in the processing and recycling of whey allow for the obtaining healthy functional food products, beverages, animal feed and other useful products and valuable solutions instead of the disposal of whey in the dairy products technologies.